Case studies in adapted physical education empowering critical thinking - Hodge, Samuel R.; Murata, Nathan M.; Block, Martin E. 1958-; Lieberman, Lauren J. 1965- (New York, NY Routledge, 2020)
"Covering self-contained adapted physical education classes, general physical education programs, as well as youth sports and community recreation, this book presents a series of case studies of teaching individuals of varied ability and disability in physical activity settings. Outlining realistic scenarios, it encourages an interactive, problem-solving teaching and learning style, and the development of critical thinking skills. Now in a fully revised and updated second edition, the book covers a wide range of different professional issues, themes, disabilities and conditions, from assessment and behavior management processes to working with students with intellectual disabilities, motor difficulties, chronic illness or obesity. Each case study includes questions that challenge the reader to reflect on the practical issues involved and how to build inclusive teaching strategies. This book is valuable reading for all physical education students, teacher candidates, and novice and experienced teachers looking to deepen their understanding of adapted physical education and to improve their professional practice. It is an essential companion to any adapted physical education or physical activity course"--
1. Changing attitudes: out of the shadows into the gym -- 2. Teachers navigating placement decisions -- 3. Culturally sustainable and relevant pedagogy in physical education -- 4. Inclusion without accompaniment -- 5. Support personnel -- 6. Creating and conducting a self-contained APE program -- 7. Consultation: PE generalist and APE specialist -- 8. Evaluating skills development: TGMD-3 -- 9. Evaluating physical fitness: Brockport -- 10. Are integrated physical education classes inclusive? -- 11. Peer tutoring for physical education -- 12. Teaching students with speech and language impairments -- 11. Peer tutoring for physical education -- 12. teaching students with speech and language impairments -- 13. Technological applications in physical education -- 14. A team approach to inclusion -- 15. Student with disabilities on the playground -- 16. After-school sports -- 17. Addressing the motor domain through the IEP/ITP process -- 18. Opportunities for adults at their local recreation center -- 19. Taking advantage of membership in a local health club -- 20. Social inclusion of students with physical disabilities -- 21. Principles of behavior management -- 22. Reinforcement to increase appropriate behaviors -- 23. Punishment to decrease or eliminate misbehavior -- 24. Strategies in resolving conflict -- 25. Teaching students with learning disabilities -- 26. Teaching students with attention deficit disorder and hyperactivity -- 27. Teaching students with developmental coordination disorder -- 28. Teaching students with intellectual disabilities -- 29. Teaching students with disabilities: the itinerant adapted PE teacher -- 30. Teaching students who are hard at hearing -- 31. Teaching students with visual impairments -- 32. Teaching students with CHARGE syndrome -- 33. Teaching a student with a severe disability -- 34. Teaching students with severe Spatic Cerebral Palsy -- 35. Teaching students with Autism Spectrum Disorder -- 36. Teaching students with motor delay and mobility difficulties -- 37. Teaching students with seizure disorders -- 38. Teaching students with physical disabilities -- 39. Teaching students with asthma -- 40. teaching students with diabetes and obesity
Includes bibliographical references and index
Keywords: Physical education for children with disabilities -- Study and teaching -- Case studies